Endovascular Device for Endothelial Cell Sampling. Issue 10 (21st August 2022) - Sandell, Mikael; Chireh, Arvin; Spyrou, Argyris; Grankvist, Rikard; Al-Saadi, Jonathan; Jonsson, Stefan; van der Wijngaart, Wouter; Stemme, Göran; Holmin, Staffan; Roxhed, Niclas
Abstract : Endothelial cells play an important role in several vascular diseases, and molecular analysis of these cells could provide valuable information on underlying tissue status. However, no clinically established procedure for harvesting endothelial cells exists. A micro‐3D‐printed device adapted for endovascular techniques to harvest endothelial cells for transcriptomic analysis is presented. In vivo evaluation in swine ( n = 6) yielded tissue samples in 60 out of 65 cases, of which 80% show a substantial amount of tissue. The cytological evaluation indicates high selectivity towards endothelial cells, and RNA‐sequencing shows gene expression signatures consistent with vascular tissue. It is found that there are no short‐term safety risks compared to operation with a control wire of equal dimensions and acute complications are not detected. If translated to clinical use, the device could enable increased understanding of early‐stage endothelial cell‐mediated disease progression and earlier diagnosis of diseases such as atherosclerosis. Abstract : An endovascular device is designed that enables minimally invasive sampling of the endothelium of peripheral vessels. The catheter is constructed with 3D‐printed brush structures assembled on a sub‐mm nitinol wire and is housed inside a polytetrafluoroethylene tube with an outer diameter smaller than 0.5 mm.